Pengaruh Karakteristik Perusahaan Terhadap Corporate Social Responsibility Disclosure pada Perusahaan yang Terdaftar di Jakarta Islamic Index - Reza Mubarak; Rita Septiawati (Shafin: Sharia Finance and Accounting Journal, 2021)
Companies in general have their own characteristics, including those listed on the Jakarta Islamic Index (JII). Companies that enter the JII calculation are motivated by the criteria set by the MUI DSN as a condition for the company's entry into JII. Based on this, there are two problems that become the main study in this research, namely: first, is there an effect of Company Size, Profitability and Leverage on the Corporate Social Responsibility Disclosure in companies listed in JII: second, which one has more dominant influence between company size, profitability , and Leverage on Corporate Social Responsibility Disclosure at companies registered with JII. This study uses a quantitative approach. Sources of data obtained by using secondary data using the financial statements of companies listed in the Jakarta Islamic Index. The results of this study indicate that company size does not have an influence on corporate social responsibility because basically companies that have a large-scale disclosure of their corporate social responsibility are getting wider. In addition, ROA has a significant negative effect on Corporate Social Responsibility in the Jakarta Islamic Index company. And also, DER does not have a significant effect on the Corporate Social Responsibility Disclosure of companies listed in JII.